2020
DOI: 10.21831/jpji.v16i2.31083
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan jasmani, olahraga, dan kesehatan di sekolah dasar: deskripsi permasalahan, urgensi, dan pemahaman dari perspektif guru

Abstract: Sejarah yang begitu panjang dalam mempertahankan eksistensi pendidikan jasmani dan olahraga di Indonesia, masih belum bisa memberikan sebuah ‘oase’ atau pengalaman yang menyenangkan di tengah permasalahan-permasalahan yang semakin menjustifikasi ketidakbermanfaatan pendidikan jasmani di sekolah maupun masyarakat. Tujuan penelitian ini berusaha untuk mengungkap gambaran tentang permasalahan, urgensi, dan pemahaman dalam pembelajaran pendidikan jasmani di sekolah dasar dari perspektif guru. Metode penelitian men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Besides, they play games to the level of addiction, which reduces physical activity and interferes with function, brain, and performance, negatively impacting health (Chan et al, 2022;Yin, 2020). Irmansyah et al (2020) concluded that all parties need awareness to reconstruct the physical education learning system to improve and improve the quality of teachers and physical education learning, which at least starts with the physical education teacher himself. It is also supported by Damrah et al (2020), stating that teacher performance in pedagogic abilities, professional abilities and social abilities requires special attention to better carry out the teacher's duties and obligations.…”
Section: Regulation Of the Minister Of Education Number 41 (2007) Con...mentioning
confidence: 99%
“…Besides, they play games to the level of addiction, which reduces physical activity and interferes with function, brain, and performance, negatively impacting health (Chan et al, 2022;Yin, 2020). Irmansyah et al (2020) concluded that all parties need awareness to reconstruct the physical education learning system to improve and improve the quality of teachers and physical education learning, which at least starts with the physical education teacher himself. It is also supported by Damrah et al (2020), stating that teacher performance in pedagogic abilities, professional abilities and social abilities requires special attention to better carry out the teacher's duties and obligations.…”
Section: Regulation Of the Minister Of Education Number 41 (2007) Con...mentioning
confidence: 99%
“…The positive self-assessment attitude of teachers, demonstrated through everyday behavior, can be emulated by their students, enabling them to also develop a positive self-assessment. Maksum (Irmansyah, et al, 2020) has shown that many physical education teachers lack in various aspects, including scientific knowledge, teaching skills, understanding of the substance of each sports branch, low critical thinking ability, limited creativity in problem-solving, lack of motivation to improve competence, and inadequate collaboration and discourse for critical exchange of ideas and experiences. This research will focus on the study and analysis of the squat style in long jump (Prasetyo, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…As support for learning, teaching guidelines are part of a teaching material that is structured in a structured and easy-tounderstand language for students with the help of educators (Puspitasari, 2019). One of the problems in the implementation of physical education in general elementary schools is the lack of understanding of teachers regarding the concept of physical education learning and the incompatibility of the concept with the practice of learning physical education (Irmansyah et al, 2020). While the basic problem in teaching student with autism is the lack of teacher books/modules and student books (Ardianingsih et al, 2017).…”
Section: Introductionmentioning
confidence: 99%